2007
DOI: 10.1177/153303460700600504
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Theorectical Radiation Dose Enhancement from Nanoparticles

Abstract: Recently, nanoparticles have been considered as a method of providing radiation dose enhancement in tumors. In order to quantify this affect, a dose enhancement factor (DEF) is defined that represents the ratio of the dose deposited in tumor with nanoparticles, divided by the dose deposited in the tumor without nanoparticles. Materials with atomic numbers (Z) ranging from 25 to 90 are considered in this analysis. In addition, the energy spectrum for a number of external beam x-ray sources and common radionucli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
127
3
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 37 publications
8
127
3
4
Order By: Relevance
“…Among all the situations evaluated, the highest electron dose enhancement obtained was 1.08, which was that of 30 mg/ml Au nanoparticles with 8 MeV electron beams (Table 2). Although this level of dose enhancement is not as high as the levels obtained by brachytherapy photon sources in previous studies [3,6,22], it seems to be a clinically signifi cant value, because it corresponds to an 8% dose enhancement inside the tumor. The fact that the observed dose enhancement for electron beam therapy is lower than brachytherapy depends on the voxelization adopted in these two modalities.…”
Section: Discussioncontrasting
confidence: 54%
“…Among all the situations evaluated, the highest electron dose enhancement obtained was 1.08, which was that of 30 mg/ml Au nanoparticles with 8 MeV electron beams (Table 2). Although this level of dose enhancement is not as high as the levels obtained by brachytherapy photon sources in previous studies [3,6,22], it seems to be a clinically signifi cant value, because it corresponds to an 8% dose enhancement inside the tumor. The fact that the observed dose enhancement for electron beam therapy is lower than brachytherapy depends on the voxelization adopted in these two modalities.…”
Section: Discussioncontrasting
confidence: 54%
“…A further modelling study compared GNP dose enhancement with a range of X-ray energies, including commonly used brachytherapy radioisotopes, demonstrating, as expected, that high-Z materials at lower photon energies would be predicted to yield the greatest physical enhancement [61]. It was noted that even in the superficial and orthovoltage kilovoltage range, where photoelectric interactions are dominant, significant enhancement would occur only if uniform GNP concentrations were greater than 1 mg ml -1 .…”
Section: Monte Carlo Modelling Studiesmentioning
confidence: 74%
“…Hainfeld et al further proved that adding gold nanoparticle in radiotherapy is efficacious when treating highly aggressive squamous cell carcinoma using the small animal model [8]. To quantify the dose enhancement due to the heavy atom nanoparticle addition, Roeske et al estimated the dose enhancement factor based on the effective mass energy coefficient and concluded that heavy atom nanoparticle coupled with low-energy photons has the potential of significantly enhancing the delivered dose [9].…”
Section: Introductionmentioning
confidence: 98%